Art therapy as a nursing intervention for people with schizophrenia - Nabila Bulan Safitri; Muhammad Ari Arfianto; Wachid Abddillah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Patients experiencing auditory hallucinations are characterized by hearing whispers or seeing shadows and experiencing sensations through their senses of touch, smell, taste, sight, and hearing. Purpose: To evaluate the effectiveness of occupational drawing therapy in reducing auditory hallucinations in patients with schizophrenia. Method: Data collection on the respondents' cases used a descriptive case study design, with art therapy intervention provided. The intervention was conducted over three days. One respondent was treated with a nursing problem of sensory perception disorder (SPD) and hallucinations. Data collection was conducted before and after the procedure using the AHRS questionnaire and a checklist of signs and symptoms of hallucinations based on the Indonesian Child Health Association (IDHS). This intervention was administered over three days, with each session lasting 45 minutes. Results: Drawing therapy has been shown to reduce the signs and symptoms of hallucinations. Before therapy, the patient's AHRS score was 11, categorized as severe, and the observation of signs and symptoms was 9. After therapy, the score decreased to 4, categorized as mild, and the observation of signs and symptoms was 2. Conclusion: This additional intervention can be used as a reference for non-pharmacological therapy considerations because it has been proven effective in reducing the signs and symptoms of hallucinations. Keywords: Drawing Therapy; Hallucinations; Schizophrenia.